Financial Technology in Indonesia: Effect of Risk on Financial Performance in Peer-To-Peer Lending - Putri, Bella Marcelina; Wibisono, C Handoyo (KINERJA, 2022)
This study aims to acquire empirical evidence related to the effect of risk on financial performance in peer-to-peer lending in Indonesia. By exploring the financial statements throughout 2019-2020. The test uses a panel data regression model, the Common Effect Model as the selected estimation regression model. Financial risk is measured by Operating Income Operating Expenses (BOPO), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Capital Adequacy Ratio (CAR). In contrast, financial performance is measured by Return on Assets (ROA) and Return on Equity (ROE). The results of this study showed that the solvency risk projected by DAR, DER, and CAR had proven to influence the profitability of peer-to-peer lending in Indonesia projected by both ROA and ROE.